Apelin is expressed throughout the human kidney, is elevated in chronic kidney disease & associates independently with decline in kidney function. Issue 12 (19th July 2022) - Nyimanu, Duuamene; Chapman, Fiona A.; Gallacher, Peter J.; Kuc, Rhoda E.; Williams, Thomas L.; Newby, David E.; Maguire, Janet J.; Davenport, Anthony P.; Dhaun, Neeraj
Abstract : Aims: Chronic kidney disease (CKD) is common and cardiovascular disease (CVD) is its commonest complication. The apelin system is a potential therapeutic target for CVD but data relating to apelin in CKD are limited. We examined expression of the apelin system in human kidney, and investigated apelin and Elabela/Toddler (ELA), the endogenous ligands for the apelin receptor, in patients with CKD. Methods: Using autoradiography, immunohistochemistry and enzyme‐linked immunosorbent assay, we assessed expression of apelin, ELA and the apelin receptor in healthy human kidney, and measured plasma apelin and ELA in 155 subjects (128 patients with CKD, 27 matched controls) followed up for 5 years. Cardiovascular assessments included blood pressure, arterial stiffness (pulse wave velocity) and brachial artery flow‐mediated dilation. Surrogate markers of endothelial function (plasma asymmetric dimethylarginine and endothelin‐1) and inflammation (C‐reactive protein and interleukin‐6) were measured. Results: The apelin system was expressed in healthy human kidney, throughout the nephron. Plasma apelin concentrations were 60% higher in women than men (6.48 [3.62–9.89] vs . 3.95 [2.02–5.85] pg/mL; P < .0001), and increased as glomerular filtration rate declined ( R = −0.41, P < .0001), and albuminuria rose ( R = 0.52, P < .0001). Plasma apelin and ELA were associated with vascular dysfunction. Plasma apelin associated independently with a 50% decline in glomerular filtration rate at 5 years. Conclusion: We show for the first time that the apelin system is expressed in healthy human kidney. Plasma apelin is elevated in CKD and may be a potential biomarker of risk of decline in kidney function. Clinical studies exploring the therapeutic potential of apelin agonism in CKD are warranted.